Combining non‐invasive brain stimulation with functional magnetic resonance imaging to investigate the neural substrates of cognitive aging. Issue 5 (16th August 2019) - Abellaneda‐Pérez, Kilian; Vaqué‐Alcázar, Lídia; Solé‐Padullés, Cristina; Bartrés‐Faz, David
Abstract: As aging population is increasing, new methodologies to apprehend and enhance the mechanisms related to optimal brain function in advancing age become urgent. This review describes how the combined use of non‐invasive brain stimulation (NIBS) with functional magnetic resonance imaging (fMRI) provides novel experimental data on the putative neurophysiological mechanisms underlying inter‐individual differences in cognitive status among older adults, also further illuminating our understanding of theoretical models proposed within the cognitive neuroscience of aging literature. In addition, it explores published evidence of how this combined procedure entails the capacity to modify the activity and connectivity of specific brain networks in older adults, potentially leading to improvements in cognitive function and other measures reflecting mental health status. Although additional research is needed, combining NIBS with fMRI might provide innovative understanding of how fundamental brain plasticity mechanisms operate in advancing age, a knowledge that may be eventually used to refine more individually tailored approaches to promote brain health in aged populations.